Diesel Engines and Biodiesel Engines Technologies - Inambao, Freddie L. (IntechOpen, 2022)
Diesel Engines and Biodiesel Engines Technologies explores the conceptual and methodological approaches for the understanding of both diesel engines and biodiesel technologies. The book incorporates reviews of the most significant research findings in both diesel and biodiesel engine production and utilization. It presents technological interventions in biodiesel production and offers a foresight analysis of the perspectives of biodiesel as a future global commodity. It also examines the main challenges that biodiesel will have to overcome in order to play a key role in future energy systems. Furthermore, the book discusses alternative diesel fuels from oils and fats and proposes solutions to issues associated with biodiesel feedstocks, production issues, quality control, viscosity, stability, applications, emissions, and other environmental impacts.